HEAT-RESISTANT MECHANICALLY ALLOYED ALUMINIUM MATERIALS WITH LOW COEFFICIENT OF LINEAR EXPANSION - G. F. Lovshenko; E. I. Marukovich (Литьë и металлургия)
The conformities of forming and characteristics of the composition heat-resistant mechanically alloyed aluminium materials with low coefficient of foundry expansion on the basis of the system Al-Si are presented and perspective of their application for engine- and instrument-making is shown.